Gel catalyst for treating organic pollutants and preparation method and application thereof

By using iron-doped polyphenol-formaldehyde resin microspheres and nanoferrates and other materials in the photofenton technology, the problems of poor catalyst activity and poor recovery in the prior art are solved. Efficient degradation of organic pollutants and reusable catalysts are achieved.

CN118874541BActive Publication Date: 2025-02-11GUIZHOU MATERIAL IND TECH INSTITUE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410932322.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-02-11
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

In the existing photofenton technology, homogeneous catalysts contain large amounts of iron sludge and narrow pH range, while heterogeneous catalysts have problems such as poor activity and poor catalyst recovery repeatability.

Method used

Through the combination of iron-doped polyphenol-formaldehyde resin microspheres, nanoferrate, acrylic acid, and ammonium persulfate, heterogeneous gel catalytic materials are prepared to form S-type heterojunctions to enhance visible light response and Catalytic activity and improve the suspension and reusability of the catalyst through the three-dimensional porous structure and hydrophilicity of the polyacrylic gel.

Benefits of technology

The activity of the catalyst and the efficiency of visible light utilization are improved, the ability to degrade and remove organic pollutants is enhanced, and the reusable and efficient removal efficiency of the catalyst is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118874541B_ABST
    Figure CN118874541B_ABST
Patent Text Reader

Abstract

The present application provides a gel catalyst for treating organic pollutants, and its preparation method and application, which belongs to the technical field of organic pollutant treatment. The preparation method provided in the present application includes the following steps: placing polyphenols, formaldehyde and an iron source in water, adding a catalyst to stir and dissolve, transferring the obtained solution to a reactor for reaction, taking the solution after the reaction, cooling and filtering in turn to obtain a filter residue, washing the filter residue to obtain iron-doped polyphenol-formaldehyde resin microspheres; mixing the iron-doped polyphenol-formaldehyde resin microspheres and nano-ferrite in a certain proportion by ball milling to obtain a composite material; placing acrylic acid, a cross-linking agent, and ammonium persulfate in water and stirring evenly, and then adding a certain amount of the composite material, standing under water bath heating conditions to obtain a hydrogel, and freeze-drying the hydrogel to obtain a gel catalyst. The present application can solve the problems of poor activity of heterogeneous catalysts and poor reproducibility of catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of organic pollutant treatment, and specifically relates to a gel catalyst for organic pollutant treatment, a preparation method and an application thereof. Background Art

[0002] In wastewater treatment processes, advanced oxidation processes are usually used to convert refractory organic pollutants into more degradable or less toxic compounds by producing strong oxidizing substances.

[0003] As a typical advanced oxidation process, photo-Fenton technology mainly utilizes photocatalytic reaction and Fenton reagent (usually Fe 2+ and H2O2) to produce highly oxidizing hydroxyl radicals (·OH), thereby efficiently oxidizing and decomposing organic pollutants.

[0004] The photocatalysts used in photo-Fenton technology are divided into homogeneous catalysts and heterogeneous catalysts. The homogeneous catalyst and the reactants are in the same phase without phase boundaries, which enables the catalytic reaction to proceed efficiently. However, the homogeneous catalyst has problems such as large iron sludge and narrow pH range. The heterogeneous catalyst and the reactants are in different phases, which makes the separation of the catalyst and wastewater easier and can solve the problems of large iron sludge and narrow pH range for homogeneous catalysts. However, the heterogeneous catalyst has problems such as poor activity and poor catalyst recyclability.

[0005] Therefore, it is necessary to provide a gel catalyst for treating organic pollutants and a preparation method and application thereof to solve the problems raised in the above background technology. Summary of the invention

[0006] The present application provides a gel catalyst for treating organic pollutants, a preparation method and an application thereof. A heterogeneous gel catalytic material is obtained by compounding iron-doped polyphenol-formaldehyde resin microspheres, nano-ferrite, acrylic acid and ammonium persulfate, which can solve the problems of poor activity of heterogeneous catalysts and poor catalyst recyclability and repeatability mentioned in the background technology.

[0007] In order to solve the above technical problems, the technical solution of this application is:

[0008] The present application provides a method for preparing a gel catalyst for treating organic pollutants, comprising the following steps:

[0009] Step S1, placing polyphenols, formaldehyde and an iron source in water, adding a catalyst and stirring to dissolve, transferring the obtained solution to a reactor for reaction, cooling and filtering the solution after the reaction in sequence to obtain a filter residue, and washing the filter residue to obtain iron-doped polyphenol-formaldehyde resin microspheres;

[0010] Step S2, ball-milling and mixing the iron-doped polyphenol-formaldehyde resin microspheres and nano-ferrite in a certain ratio to obtain a composite material;

[0011] Step S3, placing acrylic acid, a cross-linking agent, and ammonium persulfate in water and stirring them evenly, then adding a certain amount of the composite material, and standing it in a water bath under heating conditions to obtain a gel material after cross-linking is completed.

[0012] As an improvement, the polyphenol is selected from at least one of phenol, tea polyphenols and resorcinol; the iron source is selected from any one of ferric chloride, ferrous sulfate, ferrous oxalate, ferric citrate and iron carbon dots; the catalyst is selected from any one of boric acid, acetic acid, oxalic acid, ammonia water and triethylamine.

[0013] As an improvement, the mass ratio of the polyphenols to formaldehyde is 1:2.

[0014] As an improvement, in step S1, the reaction temperature of the solution in the reactor is 180-250°C, and the reaction time is 10-30 minutes; the cleaning liquid used for washing the filter residue is ethanol.

[0015] As an improvement, in step S2, the nano ferrite is selected from any one of manganese ferrite, zinc ferrite, barium ferrite, cobalt ferrite, and nickel ferrite; and the added mass ratio of the iron-doped polyphenol-formaldehyde resin microspheres to the ferrite is 1:10-10:1.

[0016] As an improvement, in step S2, the ball milling speed is 500-5000 rpm, and the ball milling time is 5-50 s.

[0017] As an improvement, in step S3, the cross-linking agent is N,N′-methylenebisacrylamide, and its content is 0.2-0.6% of the acrylic acid content; the ammonium persulfate content is 2-4% of the acrylic acid content; and the water content is 5 times the acrylic acid content.

[0018] The present application also provides a gel catalyst for treating organic pollutants, which is prepared using the above-mentioned preparation method.

[0019] The present application also provides an application of the above-mentioned gel catalyst for treating organic pollutants, which is used for adsorbing organic pollutants in wastewater under light conditions.

[0020] As an improvement, the organic pollutant is chloroquine phosphate, methylene blue or tetracycline.

[0021] The beneficial effects of this application are:

[0022] (1) During the ball milling process, iron-doped polyphenol-formaldehyde resin microspheres and nanoferrites form an S-type heterojunction, and the e- and h + It can be effectively separated under the action of the built-in electric field, which enhances the visible light response range and catalytic activity;

[0023] (2) The composite material contains hydrophilic groups such as hydroxyl groups, which can be dispersed in an acrylic acid monomer solution. After standing and cross-linking, the photocatalytic material is evenly dispersed on the single-side surface of the hydrogel. After freeze-drying, the formed hydrogel has a photocatalytic active layer and a three-dimensional porous polyacrylic acid gel layer evenly distributed on the surface, ensuring that the gel catalyst can be suspended in water for surface photocatalysis, further improving the utilization of visible light and the exposure of catalytic active sites, while also avoiding the interference of colored substances in the water on light absorption and catalysis, thereby improving the degradation and removal capacity of pollutants under visible light radiation;

[0024] (3) The gel catalyst has the porous structure and hydrophilicity of aerogel, which can continuously adsorb wastewater into the pores for surface photocatalysis, thereby improving the removal efficiency of organic pollutants through the adsorption-catalytic oxidation process;

[0025] (4) The carboxyl and amino groups on the surface of the polyacrylic acid gel can form hydrogen bonds with the hydroxyl groups of the catalytic material, so that the catalytic material is firmly fixed on its surface, preventing the catalytic material from falling off during use, so that the gel catalyst can be used repeatedly. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which:

[0027] Figure 1 The surface SEM image of the gel catalyst in Example 3 is shown;

[0028] Figure 2 represents a cross-sectional SEM image of the gel catalyst in Example 3;

[0029] Figure 3 The graphs show the degradation of chloroquine phosphate by the gel catalyst samples prepared in different embodiments. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0031] Please refer to Figure 1-Figure 3 The present application provides a method for preparing a gel catalyst for treating organic pollutants, comprising the following steps:

[0032] Step S1, placing polyphenols, formaldehyde and an iron source in water, adding a catalyst and stirring to dissolve, transferring the obtained solution to a reactor for reaction, cooling and filtering the solution after the reaction in sequence to obtain a filter residue, and washing the filter residue to obtain iron-doped polyphenol-formaldehyde resin microspheres;

[0033] Step S2, ball-milling and mixing the iron-doped polyphenol-formaldehyde resin microspheres and nano-ferrite in a certain ratio to obtain a composite material;

[0034] Step S3, placing acrylic acid, a cross-linking agent, and ammonium persulfate in water and stirring them evenly, then adding a certain amount of the composite material, and standing it in a water bath under heating conditions to obtain a gel material after cross-linking is completed.

[0035] In step S1, the polyphenol is selected from at least one of phenol, tea polyphenol and resorcinol; the iron source is selected from any one of ferric chloride, ferrous sulfate, ferrous oxalate, ferric citrate and iron carbon dots; the catalyst is selected from any one of boric acid, acetic acid, oxalic acid, ammonia water and triethylamine. The mass ratio of the polyphenol to formaldehyde is 1:2. The reaction temperature of the solution in the reactor is 180-250°C, and the reaction time is 10-30min; the cleaning liquid used for washing the filter residue is ethanol.

[0036] In step S2, the nano ferrite is selected from any one of manganese ferrite, zinc ferrite, barium ferrite, cobalt ferrite, and nickel ferrite; the added mass ratio of the iron-doped polyphenol-formaldehyde resin microspheres to the ferrite is 1:10-10:1. The ball milling speed is 500-5000 rpm, and the ball milling time is 5-50 seconds.

[0037] In step S3, the cross-linking agent is N,N′-methylenebisacrylamide, and its content is 0.2-0.6% of the acrylic acid content; the ammonium persulfate content is 2-4% of the acrylic acid content; and the water content is 5 times of the acrylic acid content.

[0038] The present application also provides a gel catalyst for treating organic pollutants, which is prepared using the above-mentioned preparation method.

[0039] The present application also provides an application of the above-mentioned gel catalyst for treating organic pollutants, which is used for adsorbing organic pollutants in wastewater under sunlight conditions.

[0040] Example 1

[0041] This embodiment provides a method for preparing iron-doped polyphenol-formaldehyde resin microspheres, comprising the following steps:

[0042] 20 mg of iron carbon dots, 0.4 g of resorcinol and 2 mL of formaldehyde were placed in a beaker, and 0.3 mL of ammonia water and 80 mL of water were added. After magnetic stirring for 1 hour, the mixture was transferred to a 200 mL high-pressure reaction tube and reacted at 250 °C for 12 hours. After cooling, the mixture was taken out and filtered with a 0.22 μm organic filter membrane to obtain a red-black solid. The solid was washed with water and ethanol for 3 times respectively, and vacuum dried at 60 °C for 24 hours to obtain iron-doped polyphenol-formaldehyde resin microspheres.

[0043] Example 2

[0044] Weigh 15 mg of the iron-doped polyphenol-formaldehyde resin microspheres prepared in Example 1, 5 mg of BaFe 12 O 19 The mixture was ball-milled at 5000 rpm for 25 s in a 2 mL PE tube and the volume was adjusted to 4 mL with deionized water to obtain a composite material.

[0045] Example 3

[0046] 5g of acrylic acid and 20g of water were placed in a 50mL beaker and stirred; 0.15g of ammonium persulfate and 25mg of N,N′-methylenebisacrylamide were added and stirred for 2h. After standing, 0.5mL of the composite material prepared in Example 2 was added and precipitated naturally for 24h. The beaker was placed in a 60°C water bath for 4h to obtain a hydrogel; the hydrogel was freeze-dried for 24h and taken out to obtain a gel catalyst.

[0047] Please refer again Figure 1-2 ,from Figure 1 It can be seen that the surface of the gel catalyst contains a uniformly distributed photocatalytic active layer and a three-dimensional porous polyacrylic acid gel layer. Surface photocatalysis can improve the utilization of visible light and the exposure of catalytic active sites, while also avoiding the interference of colored substances in the water on light absorption and catalysis, and can improve the degradation and removal capacity of pollutants under visible light radiation. Figure 2 It can be seen that the cross-sectional pores of the gel catalyst have a mesh structure, which can continuously adsorb wastewater into the pores and on the membrane surface. The removal efficiency of organic pollutants can be greatly improved through the adsorption-catalytic oxidation process. At the same time, the mesh pore structure ensures that the gel catalyst can be suspended in water.

[0048] Example 4

[0049] Weigh 2 mg of the iron-doped polyphenol-formaldehyde resin microspheres prepared in Example 1, 18 mg of BaFe 12 O 19 The mixture was ball-milled at 5000 rpm for 25 s in a 2 mL PE tube and the volume was adjusted to 4 mL with deionized water to obtain a composite material;

[0050] Place 5g of acrylic acid and 20g of water in a 50mL beaker and stir well. Add 0.15g of ammonium persulfate and 25mg of N,N′-methylenebisacrylamide, continue stirring for 2h, let stand, add 0.5mL of the prepared composite material, and precipitate naturally for 24h. Place the beaker in a 60℃ water bath for 4h to obtain a hydrogel; freeze-dry the hydrogel for 24h and take it out to obtain a gel catalyst.

[0051] Example 5

[0052] Weigh 10 mg of the iron-doped polyphenol-formaldehyde resin microspheres prepared in Example 1, 10 mg of BaFe 12 O 19 The mixture was ball-milled at 5000 rpm for 25 s in a 2 mL PE tube and the volume was adjusted to 4 mL with deionized water to obtain a composite material;

[0053] Place 5g of acrylic acid and 20g of water in a 50mL beaker and stir well. Add 0.15g of ammonium persulfate and 25mg of N,N′-methylenebisacrylamide, continue stirring for 2h, let stand, add 0.5mL of the prepared composite material, and precipitate naturally for 24h. Place the beaker in a 60℃ water bath for 4h to obtain a hydrogel; freeze-dry the hydrogel for 24h and take it out to obtain a gel catalyst.

[0054] Example 6

[0055] Weigh 15 mg of the iron-doped polyphenol-formaldehyde resin microspheres prepared in Example 1, 5 mg of BaFe 12 O 19 The mixture was ball-milled at 5000 rpm for 25 s in a 2 mL PE tube and the volume was adjusted to 4 mL with deionized water to obtain a composite material;

[0056] Place 5g acrylic acid and 20g water in a 50mL beaker and stir well. Add 0.10g ammonium persulfate and 25mg N,N′-methylenebisacrylamide and continue stirring for 2h. After standing, add 0.5mL of the prepared composite material and precipitate naturally for 24h. Place the beaker in a 60℃ water bath for 4h to obtain a hydrogel. Freeze-dry the hydrogel for 24h and take it out to obtain a gel catalyst.

[0057] Example 7

[0058] Weigh 15 mg of the iron-doped polyphenol-formaldehyde resin microspheres prepared in Example 1, 5 mg of BaFe 12 O 19 The mixture was ball-milled at 5000 rpm for 25 s in a 2 mL PE tube and the volume was adjusted to 4 mL with deionized water to obtain a composite material;

[0059] Place 5g of acrylic acid and 20g of water in a 50mL beaker and stir well. Add 0.15g of ammonium persulfate and 10mg of N,N′-methylenebisacrylamide, continue stirring for 2h, let stand, add 0.5mL of the prepared composite material, and precipitate naturally for 24h. Place the beaker in a 60℃ water bath for 4h to obtain a hydrogel; freeze-dry the hydrogel for 24h and take it out to obtain a gel catalyst.

[0060] Weigh 10 mg of each sample obtained in Example 1 and Example 2, and the samples obtained in Examples 3-7, and place them in 50 mL of an organic pollutant solution, wherein the content of chloroquine phosphate in the organic pollutant solution is 20 mg / L; stir for 30 min in the dark to achieve adsorption equilibrium, turn on the condensation circulating water, and take 2 mL of the solution from the above solution every 5-10 minutes under irradiation of a 300 W xenon lamp (with a 420 nm filter), pass through a 0.22 μm filter membrane, and test the change of pollutant concentration with visible light irradiation time. The test results are shown in Table 1.

[0061] Table 1 The removal effect of samples on chloroquine phosphate in Examples 1-7

[0062]

[0063]

[0064] As shown in Table 1, the samples in Examples 1-7 all achieve complete removal of chloroquine phosphate, indicating that iron-doped polyphenol-formaldehyde resin microspheres, composite materials and gel catalysts all have adsorption-visible light catalytic degradation effects on chloroquine phosphate. Wherein, in the case where the usage amount is halved, Examples 3-7 still ensure complete removal of chloroquine phosphate, while also greatly shortening the time required for catalysis, and increasing the adsorption amount of chloroquine phosphate. The reason is that: the hydrophilicity of polyacrylic acid and the water absorption of the three-dimensional pore structure improve the adsorption of chloroquine phosphate on the catalyst surface, shorten the distance between free radicals and pollutants, and enhance the photocatalytic degradation efficiency.

[0065] The embodiments of the present application are described above in conjunction with the accompanying drawings, but the present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.

Claims

1. A method for preparing a gel catalyst for treating organic pollutants, characterized in that: The steps include: Step S1, placing polyphenol, formaldehyde and an iron source in water, adding a catalyst and stirring to dissolve, transferring the obtained solution to a reactor for reaction, wherein the reaction temperature of the solution in the reactor is 180-250° C., and the reaction time is 10-30 min, cooling and filtering the solution after the reaction in sequence to obtain a filter residue, and washing the filter residue to obtain iron-doped polyphenol-formaldehyde resin microspheres; Step S2, ball-milling and mixing the iron-doped polyphenol-formaldehyde resin microspheres and nano-ferrite in a certain ratio to obtain a composite material; Step S3, placing acrylic acid, a cross-linking agent, and ammonium persulfate in water and stirring them evenly, then adding a certain amount of the composite material, standing under a water bath heating condition to obtain a hydrogel, and freeze-drying the hydrogel to obtain a gel catalyst.

2. The method for preparing a gel catalyst for treating organic pollutants according to claim 1, characterized in that: The polyphenol is selected from at least one of tea polyphenol and resorcinol; the iron source is selected from any one of ferric chloride, ferrous sulfate, ferrous oxalate, ferric citrate, and iron carbon dots; the catalyst is selected from any one of boric acid, acetic acid, oxalic acid, ammonia water, and triethylamine.

3. The method for preparing a gel catalyst for treating organic pollutants according to claim 1, characterized in that: The mass ratio of the polyphenols to formaldehyde is 1:

2.

4. The method for preparing a gel catalyst for treating organic pollutants according to claim 1, characterized in that: In step S1, the cleaning liquid used to wash the filter residue is ethanol.

5. The method for preparing a gel catalyst for treating organic pollutants according to claim 1, characterized in that: In step S2, the nano ferrite is selected from any one of manganese ferrite, zinc ferrite, barium ferrite, cobalt ferrite, and nickel ferrite; and the added mass ratio of the iron-doped polyphenol-formaldehyde resin microspheres to the ferrite is 1:10-10:

1.

6. The method for preparing a gel catalyst for treating organic pollutants according to claim 1, characterized in that: In step S2, the ball milling speed is 500-5000 rpm, and the ball milling time is 5-200 s.

7. The method for preparing a gel catalyst for treating organic pollutants according to claim 1, characterized in that: In step S3, the cross-linking agent is N,N′-methylenebisacrylamide, and its content is 0.2-0.6% of the acrylic acid content; the ammonium persulfate content is 2-4% of the acrylic acid content; and the water content is 5 times of the acrylic acid content.

8. A gel catalyst for treating organic pollutants, characterized in that: The method is prepared by any one of claims 1 to 7.

9. A use of the gel catalyst for treating organic pollutants as claimed in claim 8, characterized in that: Used to adsorb organic pollutants in wastewater under light conditions.

10. The use of the gel catalyst for treating organic pollutants according to claim 9, characterized in that: The organic pollutant is chloroquine phosphate, methylene blue or tetracycline.

Citation Information

Patent Citations

  • Preparation method for gel capsule wall material used for absorbing heavy metals

    CN103495408A

  • Carbon aerogel magnetic material for treating heavy metal wastewater and preparation method

    CN109331779A